Outcomes of laboratory‐confirmed SARS‐CoV‐2 infection in the Omicron‐driven fourth wave compared with previous waves in the Western Cape Province, South Africa. Issue 6 (10th May 2022) - Davies, Mary‐Ann; Kassanjee, Reshma; Rousseau, Petro; Morden, Erna; Johnson, Leigh; Solomon, Wesley; Hsiao, Nei‐Yuan; Hussey, Hannah; Meintjes, Graeme; Paleker, Masudah; Jacobs, Theuns; Raubenheimer, Peter; et al.
Abstract: OBJECTIVES: The objective was to compare COVID‐19 outcomes in the Omicron‐driven fourth wave with prior waves in the Western Cape, assess the contribution of undiagnosed prior infection to differences in outcomes in a context of high seroprevalence due to prior infection and determine whether protection against severe disease conferred by prior infection and/or vaccination was maintained. METHODS: In this cohort study, we included public sector patients aged ≥20 years with a laboratory‐confirmed COVID‐19 diagnosis between 14 November and 11 December 2021 (wave four) and equivalent prior wave periods. We compared the risk between waves of the following outcomes using Cox regression: death, severe hospitalisation or death and any hospitalisation or death (all ≤14 days after diagnosis) adjusted for age, sex, comorbidities, geography, vaccination and prior infection. RESULTS: We included 5144 patients from wave four and 11, 609 from prior waves. The risk of all outcomes was lower in wave four compared to the Delta‐driven wave three (adjusted hazard ratio (aHR) [95% confidence interval (CI)] for death 0.27 [0.19; 0.38]. Risk reduction was lower when adjusting for vaccination and prior diagnosed infection (aHR: 0.41, 95% CI: 0.29; 0.59) and reduced further when accounting for unascertained prior infections (aHR: 0.72). Vaccine protection was maintained in wave four (aHR for outcome of death: 0.24; 95% CI: 0.10; 0.58). CONCLUSIONS: In the Omicron‐driven wave, severe COVID‐19 outcomes were reduced mostly due to protection conferred by prior infection and/or vaccination, but intrinsically reduced virulence may account for a modest reduction in risk of severe hospitalisation or death compared to the Delta‐driven wave.